Silagem de papuã ou de sorgo na terminação de bovinos: tecidos corporais e características da carcaça e da carne - Weise, Matheus Smidt (2012)
The aim of the present study was to evaluate the effect of the use of Alexander grass silage (Urochloa plantaginea) on body tissues that are not part of the carcass, as well as the quantitative and qualitative aspects of the carcass and meat from feedlot finished steers. It was used 12 castrated, pure and crossbred Charolais x Nellore steers, age and initial weight were 20 months and 245 kg respectively, distributed in two different treatments: Alexander grass silage (AS) = animals fed with 51% of Alexander silage and 49% of concentrate and, sorghum silage (SS) = animals fed with 53% sorghum silage and 47% of concentrate (control group). The diet was calculated searching to meet the minimal nutritional requirements in order to obtain an average daily weight gain of 1.2 kg/animal and, estimating a dry matter intake of 2.5 kg/100 kg alive. The experimental design used was randomized blocks with two treatments and six samples per treatment; each experimental unit consisted of one animal. The slaughter weight (SW), empty body weight (EBW) and, the relationship between EBW/SW were similar for animals in the tested roughage, with mean values of 442.66 kg, 381.45 kg and 0.86 respectively. The rumen-reticulum expressed in kg and, the gastrointestinal content in absolute or relative weight for 100 kg of empty body weight (%EBW) were higher for AS animals while, the liver in %EBW was higher for SS animals. AS animals showed higher kidney fat deposition, both in absolute weight and %EBW and, increased deposition of fat in the abomasum %EBW. However, in total numbers, the fats that are not part of the carcass did not differ between treatments. Hot carcass yield and fat thickness were similar between animals in the tested roughage, with an average of 58.8% and 4.7 mm, respectively. The same behavior was observed for meat color, texture and marbling. Nevertheless, the meat from AS animals showed a greater muscle and fat liquid loss when subjected to cooking. There was no difference in meat chemical composition between the tested roughage with mean values of 20.27, 76.17, 2.11 and 1.14% for crude protein, moisture, ether extract and mineral matter respectively.